Bioremedial Treatment of Industrial Waste Water Using Rhodobacter sphaeroides - Agrawal, P.K.; Prabha, S.; Mittal, S. (Our Nature, 2010)
This paper deals with the bioremedial treatment of industrial waste water using Rhodobacter sphaeroides. Key words: Bioremediation, Bioreactor, Rhodobacter sphaeroides DOI: 10.3126/on.v7i1.2581 Our Nature (2009) 7:237-240